2010
DOI: 10.1007/s10549-010-1295-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Hardy–Weinberg equilibrium in case–control or cohort studies or meta-analysis

Abstract: Purpose: Yu et al. [2009 Breast Cancer Res Treat 117:675-677] recently stated that testing for deviation from Hardy-Weinberg equilibrium (HWE) is necessary to identify systematic genotyping errors in case-control studies. They criticized a meta-analytic study for the deviation from HWE in the case group of one study. The aim of this paper is two-fold. First, 2 we derive recommendations on how to test for deviations from HWE in different study designs. Second, we develop a meta-analytic framework for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…A significant difference between the observed and expected genotype frequencies under Hardy-Weinberg equilibrium (HWE) may indicate genotyping error [2]. Departure from HWE can be caused by factors such as inbreeding caused by consanguinity, assortative mating, i.e., nonrandom mating, selection, or migration [3]. Although exceptions to the conditions of HWE may explain deviation, it is critical that investigators recognize the need to perform a test of HWE and then evaluate the reasons for any observed deviation.…”
mentioning
confidence: 99%
“…A significant difference between the observed and expected genotype frequencies under Hardy-Weinberg equilibrium (HWE) may indicate genotyping error [2]. Departure from HWE can be caused by factors such as inbreeding caused by consanguinity, assortative mating, i.e., nonrandom mating, selection, or migration [3]. Although exceptions to the conditions of HWE may explain deviation, it is critical that investigators recognize the need to perform a test of HWE and then evaluate the reasons for any observed deviation.…”
mentioning
confidence: 99%
“…A significant difference between the observed and expected genotype frequencies under Hardy-Weinberg equilibrium (HWE) may indicate genotyping error [2]. Departure from HWE can be caused by factors such as inbreeding caused by consanguinity, assortative mating, i.e., non-random mating, selection, or migration [3]. Although exceptions to the conditions of HWE may explain deviation, it is critical that investigators recognize the need to perform a test of HWE and then evaluate the reason(s) for any observed deviation.…”
Section: Three Electronic Databases (Pubmed Embase Andmentioning
confidence: 99%
“…When the proportion of affected subjects in a population is small, the degree of deviation from Hardy-Weinberg equilibrium is expected to be stronger in cases than in controls. As an indicator of genotyping quality, compatibility with Hardy-Weinberg equilibrium should be assessed in control groups (4). Additionally, the authors indicated that the genotype distribution in African American subjects was not within Hardy-Weinberg equilibrium.…”
Section: To the Editormentioning
confidence: 99%
“…Most studies of SLE genetics, including 6 recently published genome-wide association studies (GWAS) (3)(4)(5)(6)(7)(8), are focused on the identification of disease-associated variants. Although no analyses with adjustment for environmental risk factors were performed, these GWAS have been shown to provide useful insights into disease pathogenesis and potential new targets for treatment without the results being distorted.…”
Section: To the Editormentioning
confidence: 99%